Characterisation of Insulin at the Interface Between Two Immiscible Electrolyte Solutions - Lamichhane, Hum Bahadur (Curtin University, 2019)
The behaviour of insulin was characterised at the interface between the two immiscible electrolyte solutions (ITIES). Electroadsorbed insulin was subjected to study by Fourier transform infrared and Raman spectroscopy, to understand any secondary structure changes following electroadsorption. Following electroadsorption, insulin showed secondary structure changes which varied with the aqueous insulin concentration. At higher concentration, significant proportions of combined ß-sheet and irregular helix structures were found, while a-helical forms were dominant at lower concentration. Raman spectroscopy was insensitive to insulin following electroadsorption.